Modified depth-first search and ant colony system algorithm used in an online pre-travel plan recommender system - Alinea, Maverick Sabay (2008)
An Online Pre-Travel Plan Recommender System is an online system that recommends a set of places to visit in Davao City and the package includes a suggested itinerary to the trip. The system has two major users ? administrator and common users or the public. The administrator performs data entry and modifications of information about the places where the tourist can go and stay, travel time from one place to another and transportation to use in the trip. The system uses a Dijkstra?s algorithm to provide a default value which is used to determine the travel time from the newly inserted place to all other places stored in the database. The user or the tourist can have his/her own pre-travel plan. The users only need to input their traveling details like their budget and places of preferences. Based on the travelling details, the system will use a modified branch and bound method to recommend the set of travel packages. Each package will undergo an ant colony system algorithm to get the suggested itinerary of the trip. The packages with their corresponding suggested itinerary travel is presented for the users to choose from. It is recommended that the system must be improved before presenting it to the public. Additional traveling details are needed. Also, a better algorithm for recommending packages and for solving traveling salesman problem with time window are needed